The Emergence and Development of Ecofeminism in Literaure - P., Nazarova G.; Shakhrizoda, Rahkmatova (International Journal on Integrated Education, 2023)
Ecofeminism is a conceptual theory which suggests certain ethics and courses of action and motivates people for participating in social as well as environmental movement of consciousness. Starting as a subdivision of feminism and borrowing from ecology, socialism, Marxism and philosophy, it can be observed in the history even in the second wave of feminism, which shows that ecofeminism has a rooted context. Because, the degradation of nature is parallel with the history of colonization which starts as early as the 12th century and women’s oppression becomes a common characterics of the societies, ecofeminism is embedded within all colonial and misogynist activities as a reaction to all sorts of constraints.